The effect of temporal risk aversion on liquidity preference - Karady, G (Journal of Financial Economics, 1982)
In most instances, investors are not indifferent to risk. Their attitudes toward it influence their decisions. Temporal risk aversion, the dynamic analogue of the usual concept of risk aversion, has a marked effect on investors' decisions but is usually ignored in the literature. This paper investigates the liquidity preference of temporally risk-averse investors. The analysis shows that, all other things being equal, temporal risk aversion reduces the liquidity premium investors must receive to hold an asset that is not perfectly reversible. Thus, the optimal investment policy is closer to what one would expect had a frictionless exchange market existed for the irreversible asset. As far as an individual's investment behavior is concerned, temporal risk aversion counters the effects of an asset's irreversibility and tends to compensate for the absence of frictionless exchange.